Le genre de tullist : Etiquetage terminologique et émergence générique - Saida Mohand Saidi; Mohand Akli Salhi (Multilinguales)
The paper examines the birth of the literay genre called tullist in the amazigh language. Firstly, we focus on the denomination of this literary genre, by studying the etymology which lies at the root of the creation of the word tullist, and the evolution of its terminological uses (tullist/tullizt) both in the traditional and the contemporary genre configurations. Secondly, we deal with and discuss the presence of traditional literary terms (tamacahutt, tadyant, taqsiṭ...) at the level of the titles or in the body of texts considered as belonging to the newly-born genre tullist. The discussion aims at starting a debate on the issue of continuity and/or discontinuity in kabyle literature.